2018
DOI: 10.1038/nrd.2017.251
|View full text |Cite|
|
Sign up to set email alerts
|

Post-exposure treatments for Ebola and Marburg virus infections

Abstract: | The filoviruses -Ebola virus and Marburg virus -cause lethal haemorrhagic fever in humans and non-human primates (NHPs). Filoviruses present a global health threat both as naturally acquired diseases and as potential agents of bioterrorism. In the recent 2013-2016 outbreak of Ebola virus, the most promising therapies for post-exposure use with demonstrated efficacy in the gold-standard NHP models of filovirus disease were unable to show statistically significant protection in patients infected with Ebola vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 292 publications
(349 reference statements)
2
76
0
Order By: Relevance
“…Consistent results were reported in a retrospective analysis of 163 patients admitted in an Ebola treatment center in Coyah, Guinea, where lower but no significant case fatality rate and significant longer survival time were found in patients receiving favipiravir on a compassionate use basis 38 . Several clinical trials evaluating other candidate treatments from different therapeutic classes, including ZMapp, TKM‐Ebola, brincidofovir, and convalescent plasma were implemented in Gunea, Liberia, and Sierra Leone during the 2013–2016 outbreak, yet none of them could demonstrate a significant improvement of survival rate related to the antiviral treatment 39,40 …”
Section: Favipiravir In Humans Infected With Evdsupporting
confidence: 59%
“…Consistent results were reported in a retrospective analysis of 163 patients admitted in an Ebola treatment center in Coyah, Guinea, where lower but no significant case fatality rate and significant longer survival time were found in patients receiving favipiravir on a compassionate use basis 38 . Several clinical trials evaluating other candidate treatments from different therapeutic classes, including ZMapp, TKM‐Ebola, brincidofovir, and convalescent plasma were implemented in Gunea, Liberia, and Sierra Leone during the 2013–2016 outbreak, yet none of them could demonstrate a significant improvement of survival rate related to the antiviral treatment 39,40 …”
Section: Favipiravir In Humans Infected With Evdsupporting
confidence: 59%
“…Despite decades of research, no licensed vaccines or therapies are available to date. However, ample preclinical data on rVSV-vectored MARV vaccine candidates have been generatedoften alongside the EBOV vaccine candidates, both as a pre-exposure prophylactic as well as a postexposure vaccine (reviewed in 15,87,88 ).…”
Section: Marburg Virusmentioning
confidence: 99%
“…However, an overwhelming inflammatory cytokine release can cause an undesirable effect. Therefore, numerous research groups have currently identified and studied a variety of anti‐Ebola monoclonal antibodies (mAbs), leading to the development of several commercialized mAb cocktails as recently reviewed …”
Section: Introductionmentioning
confidence: 99%